2014
DOI: 10.3892/etm.2014.1615
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular lens implantation for patients with coloboma of the iris

Abstract: The aim of this study was to analyze the techniques for intraocular lens (IOL) implantation in patients with coloboma of the iris. A retrospective cohort study was used to analyze the degree of iris coloboma and the characteristics of the crystalline lens in 56 patients with iris coloboma. The patients with a lesser degree of coloboma of the iris and an intact lens capsule were treated by iris suture and IOL implantation into the posterior chamber. Patients with an iris coloboma confined to one quadrant, sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 16 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…5,6 Risk of complications related to iris repair—including hyphema, iris dialysis, and iritis—is further magnified by other anomalous anatomy often seen in colobomatous eyes (e.g., microphthalmos). 1,5,6…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,6 Risk of complications related to iris repair—including hyphema, iris dialysis, and iritis—is further magnified by other anomalous anatomy often seen in colobomatous eyes (e.g., microphthalmos). 1,5,6…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…3,4 In those with iris coloboma, risk of complications (including hyphema, iritis, and iris dialysis) further increases when iris repair—typically by means of pupilloplasty or artificial iris implantation—is pursued at the time of cataract surgery. 5,6…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective cohort study analyzed the degree of iris coloboma and the characteristics of the crystalline lens in 56 patients with iris coloboma. They found that various techniques for IOL implantation were selected based on the degree of iris and lens capsule coloboma and these techniques were capable of improving the vision and photophobia of the patients [10]. Khokhar S et al, reported favourable surgical outcomes with phacoemulsification in all densities of cataract with congenital choroidal Coloboma [7].…”
Section: Discussionmentioning
confidence: 99%